2013
DOI: 10.3991/ijet.v8i6.2809
|View full text |Cite
|
Sign up to set email alerts
|

The ARICE Framework: Augmented Reality in Computing Education

Abstract: Abstract-Augmented Reality (AR) is a term for a live direct or an indirect view of a physical, real-world environment whose elements are augmented by computer-generated sensory input and output including sound, graphics or haptic input and feedback mechanisms. It has been reported that the use of AR for educational purposes provided opportunities for reflection, capabilities for multiple representations, and co-design of personalized learning experiences which contribute to promote active learning. However, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…In the literature, using video podcasts has been widely recognised as an effective strategy to motivate students (Bolliger, Supanakorn, & Boggs, 2010;Kay, 2012). In some AR applications, videos have been used to present examples and/or to provide additional content (Wang, Vincenti, Braman, & Dudley, 2013). Thus, we suggest that AR applications might provide videos about the learning content to support student motivation.…”
Section: Student Support Layer Videos (Vid)mentioning
confidence: 99%
“…In the literature, using video podcasts has been widely recognised as an effective strategy to motivate students (Bolliger, Supanakorn, & Boggs, 2010;Kay, 2012). In some AR applications, videos have been used to present examples and/or to provide additional content (Wang, Vincenti, Braman, & Dudley, 2013). Thus, we suggest that AR applications might provide videos about the learning content to support student motivation.…”
Section: Student Support Layer Videos (Vid)mentioning
confidence: 99%
“…AR increases the proportional, probabilistic, combinatorial, and correlational reasoning indicators of abstract thinking skills in physics teaching [9]. Physical and perceptual involvement of students in the study of Computing Education [10], the synchronous combination of the virtual world with reality and the possibility of using it as a very interesting media for history learning [11] shows the breadth of AR technologies application. The freedom to create various functional scenarios as well as the enrichment of audio-visual accompaniment gives favorable results in Immediate-Action Commander Training [12].…”
Section: Fig 1 the Scheme Of The Competence Formation Processmentioning
confidence: 99%
“…Many studies have revealed positive effect of AR for educational purposes, such as, understanding gas properties [20], AR in computing education [21], AR as e-learning tool [22], immediate-action commander training [23], mechanical drawing [24], rail transportation [17] and modelling of human heart [25]. Based on these studies AR is very useful in educating student [26] such as increasing students' achievement and visual thinking [27], promoting collaborative and autonomous learning [28], increasing academic achievement and motivation of student [25] and increasing the interest in learning [13].…”
Section: Introductionmentioning
confidence: 99%